Coercive controlling behaviors in intimate partner violence in male same-sex relationships:A mixed-methods study. Issue 3 (3rd July 2019) - Raghavan, Chitra; Beck, Connie J.; Menke, James Michael; Loveland, Jennifer E.
Abstract: Using mixed methods, we explored the role of coercive controlling behaviors in a high-risk sample of 126 men in violent same-sex relationships. Contrary to a prediction that separate factors of physical violence and coercive control might emerge, a simple principle components analysis supported that male same-sex relationship intimate partner violence (IPV) is essentially unidimensional. Qualitative narratives supported a single latent factor solution of violence, and that coercive controlling behaviors better detect IPV dynamics within the same violent encounters (i.e., weapon use), even when compared to profiles defined by physical violence. Narratives also highlighted gender-different tactics of coercion used, underscoring importance of context-based assessments.